Design and Theoretical Study of D–A–π–A Organic Sensitizers with [1,2,5]Thiadiazolo[3,4-c]pyridine, [1,2,5]Selenadiazolo[3,4-c]pyridine, and [1,2,5]Oxadiazolo[3,4-c]pyridine π Component - O. I. Bolshakov; M. A. Grishina; A. Galushko; V. A. Potemkin; O. A. Rakitin (Journal of Chemistry)
The study concerns molecular design and theoretical study of novel prospective organic sensitizers based on D–A–π–A concept. A modification of the concept (DA–π–A) and new ways for design of organic sensitizers are proposed. The study shows that π-block plays a key role for the wavelength shift in UV-Vis spectra. An existence of element of higher periods in the π-block provides a noticeable bathochromic shift. The thienyl bridge in A-block provides a red shift with respect to phenyl bridge for [1,2,5]oxadiazolo[3,4-c]pyridines while the phenyl bridge provides a red shift with respect to thienyl bridge for [1,2,5]selenadiazolo[3,4-c]pyridines. The maximal wavelengths are observed for DA-blocks with aliphatic/alicyclic fragments we proposed. An influence of enthalpy of formation and polarity of DA-blocks on bathochromic shift is shown. The quantitative dependencies of wavelengths on the enthalpies and dipole moments are determined. The maximal oscillator strengths are observed for the planar DA-block. Therefore, the conditions for design of compounds possessing the maximal wavelengths and oscillator strengths are different: the latter presupposes the planar structure of DA-block while the first presupposes an existence of nonplanar aliphatic/alicyclic fragments. Thus, the further design of organic sensitizers should include some combination of these concepts.